Re-engineering appropriate village technology for sustainable rural educational development in Africa (2013)
Accelerated sustainable development built on Rostow's take-off theory of economic development sets the stage in grassroots development in any community. This, in our stance, was significantly supported by the use of appropriate village technology. This paper, therefore argues that, although the overriding objective of the millennium development goals is reduction of poverty in all its forms, as well as the attainment of social -well-being, much attention has not been paid to the development of indigenous knowledge in this drive. Consequently, this discourse, examined the re-engineering of appropriate village technology as advanced by indigenous knowledge base on rural education for sustainable community development in Africa. Lessons, challenges and options were advanced for policy decision and implementation.